Effects of functional fatigue on joint position sense in male elite handball players - Niederseer, D.; Mörtl, H.; Liebensteiner, M. C.; Egger, A.; Thaler, C.; Niebauer, J.; Raschner, C. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Worsening of joint position sense due to fatigue results in a worsening of performance in strength and flexibility, and furthermore coincides with an increased risk of trauma. In the present study we investigate the effect of a standardized handball specific fatigue protocol on joint position sense in male elite handball players to localize joints at risk for injury. Material and Methods: Eighteen (9 under-21 players/9 professional players) male handball players (age: 22.3±4.9 years; weight: 85.1±11.3 kg; height: 185.4±5.2 cm) participated in this trial. After a standardized warm up session the athletes participated in a fatigue protocol lasting 45 minutes and 27 seconds. It consisted of 81 accelerations, 9 throws, 18 jumps, 180 ball contacts, 234 changes in direction, 225 changes in speed and a total distance of 4680 m. Of this total distance 7.7 % (360 m) were run faster than 5.2 m/s, 26.9 % (1260 m) between 5.2 and 3.1 m/s, 30.8% (1440 m) between 3 and 1.5 m/s and 34.6 % (1620 m) slower than 1.4 m/s according to present literature on characteristics of professional handball matches. The joint angle as a measure of joint position sense was measured before and after the above protocol in the right and left hips, knees and shoulders by a gravity inclinometer (Plurimeter). The blindfolded athletes had to reproduce a random angle in a standardized position within the range of motion of the investigated joint. The difference between the angle shown and the one reproduced was calculated. Error scores were defined as the sum of two measurements for each joint. Results: The fatigue protocol was performed at an average heart rate of 145±16 bpm. The assessment of joint position sense showed a worsening in 8/18 (44 %), 11/18 (61 %) and 10/18 (56 %) of the athletes` hips, knees and shoulders, respectively. The sum of the error scores of all six investigated joints remained unchanged in 10/18 (56 %) athletes, worsened in 7/18 (39 %), and only improved in 1/18 (6 %). The mean change worsened from 29.2°±13.3° at pre-test to 40.8°±17.0° at post-test (p=0.03), i.e. +11.6°±19.2° or 37 %. On average athletes were able to reproduce angles with an error of 3°±6° (p=0.09), 2°±13° (p=0.52) and 7°±12°(p=0.02) in hips, knees and shoulders, respectively. No difference was observed comparing the dominant versus the non-dominant shoulder or under-21 athletes versus professional players. Conclusion: Joint position sense abilities worsened in the shoulders, whereas measurements for hips and knees remained essentially unchanged. Joint position sense of the shoulder, but not the hip or knee can be altered with a handball specific fatigue protocol. Sensomotoric training as well as prevention and rehabilitation of joint injuries might help to correct this important factor in handball.